Analisis Rasio Likuiditas, Solvabilitas dan Profitabilitas Terhadap Kinerja Keuangan - Shidiq, Abdan; Mala, Iva Khoiril; Sutantri (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2024)
This research was conducted to finding out how big a percentage of PT's financial performance is. Mayora Indah Tbk. using Liquidity, Solvency and Profitability ratios for the 2020-2022 period. The nature of the research in this research is qualitative research. In this research, the data used in the annual financial reports of PT. Mayora Indah Tbk. 2020-2022 period. The population in this research is all assets, equity and income of PT. Mayora Indah Tbk. The sampling technique used in this research used purposive sampling. The data collection method used by the author is using internet research data collection methods, namely collecting indirect observation data by collecting data from PT's annual financial reports. Mayora Indah Tbk. 2020-2022 period. The results of this research show that the liquidity ratio as measured using the current ratio and quick ratio shows good results for company performance, the solvency ratio as measured using the Debt to Asset Ratio is 43% for 2020 and in 2021, 2022 is 42%, and Debt to equity ratio was 73.5% in the 2020 and 2022 periods, while in 2021 it was 75.35.